Candida orthopsilosis and aureobasidium pullulans: rare fungal pathogens causing persistent skin infection - Giek, Far Chan (Insight Knowledge, 2011)
Rare fungal human skin pathogens, identified as Candida orthopsilosis and Aureobasidium pullulans were co-isolated from patient with persistant cutaneous skin infection in Singapore. This significant discovery offers knowledge to the scientific and medical community in order to stimulate research interest and to address treatment regimes of fungal infection.